1889-90 Va. Acts 118, ch. 152, § 1 - (:unkn) unknown (My University, 1890)
Banned the sale, barter, transfer, giving, or furnishing, or cause to be sold to any minor under sixteen pistols, dirks, Bowie knives. Violators fined not less than ten nor more than one hundred dollars.
Keywords: TRANSFER - MINORS